Writing the Yugoslav Wars : Literature, Postmodernism, and the Ethics of Representation - Obradović, Dragana (Book collections on Project MUSE., 2016)
"In Writing the Yugoslav Wars, Dragana Obradović analyses how the Yugoslav wars of secession helped shape the region's literary culture. Obradović argues that the crisis of the country's disintegration posed an ethical challenge to self-identified postmodernists. This book takes a transnational approach to literatures of the former Yugoslavia that have been, since the 1990s, studied separately, in line with geopolitical divisions. This post-socialist conflict was one of the moments that reshaped postmodernism for both local and international thinkers, much in the same way modernism was shaped by World War I and the advent of mechanized warfare."--